Outer membrane of Escherichia coli K-12: isolation of mutants with altered protein 3A by using host range mutants of bacteriophage K3. - Manning, P A (1976)
A series of mutants has been isolated with alterations to protein 3A of the outer membrane. These mutations map at the previously described con locus as shown by cotransduction with pyrD. Most of them do not have detectable levels of protein 3A but are thought to have low levels of altered protein. These mutants have been detected by screening con mutants, isolated as resistant to bacteriophage K3, for their ability to plaque host range mutants of this bacteriophage. These host range phage mutants have activity spectra on the various con mutants that enable the bacterial mutants to be arranged in an order of increasing resistance to the host range phage mutants, from mutants sensitive to all host range phage to those sensitive to only one class. Likewise, the phage can be arragned in an order of increasing ability to plaque on the con mutants. Some of the mutants resemble the previously described con mutants in being tolerant to colicins K and L, and others resemble them in being highly defective as recipients with the F factor. These properties vary independently, suggesting that protein 3A can be modified to independently affect the three properties of bacteriophage receptor function, involvement in colicin sensitivity, and involvement in conjugation.